2013
DOI: 10.1080/19443994.2013.781106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the different filter media in vertical flow stormwater wetland

Abstract: A B S T R A C TThe performance of four different types of filter media, namely woodchip, pot gravel, synthetic fiber, and volcanic stone employed as the main media in a set of column vertical flow stormwater wetlands were evaluated in this study. The evaluation parameters were treatment performance, adsorption capacity, porosity, filtration type, plant growth, substance release, cost, and construction. For pollutant removal, all the media showed efficient reduction of total suspended solids (more than 80%). Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Among the artificial materials that have been used as a medium in CWs for N removal, ceramsite [58], activated carbon [59], synthetic fiber [60,61], cement clinker [62], recycled concrete [63], and modified clays [64] can be mentioned.…”
Section: Substrate Materialsmentioning
confidence: 99%
“…Among the artificial materials that have been used as a medium in CWs for N removal, ceramsite [58], activated carbon [59], synthetic fiber [60,61], cement clinker [62], recycled concrete [63], and modified clays [64] can be mentioned.…”
Section: Substrate Materialsmentioning
confidence: 99%
“…Orhan and Buyukgungor (2000) studied the biodegradability of polyethylene films in soil and found that the soil with higher microbial enrichment showed higher degradability capacity of polyethylene films. However, in our previous study, the same fiber was used to treat urban stormwater but no indication of the release of organic matters was observed, which may be due to the low microbial population in the urban stormwater (Chen et al, 2013).…”
Section: Removal and Release Of Organic Mattersmentioning
confidence: 99%